A cost-saving algorithm for rapid diagnosis of Staphylococcus aureus and susceptibility to oxacillin directly from positive blood culture bottles by combined testing with BinaxNOW® S. aureus and Xpert MRSA/SA assay - Yossepowitch, Orit; Dan, Michael; Kutchinsky, Anuta; Gottesman, Tamar; Schwartz–Harari, Orna (Diagnostic microbiology and infectious disease, 2014)
We studied an algorithm combining 2 rapid methods to detect Staphylococcus aureus and its susceptibility to oxacillin directly from positive blood cultures; our goal was to reduce the cost of the procedure, while maintaining accuracy and a short turnaround time. A total of 581 blood cultures containing gram-positive cocci in clusters were tested by BinaxNOW® Staphylococcus aureus Test. Positive samples were further assessed by the Xpert MRSA/SA BC Assay. Phenotypic methods have identified coagulase-negative staphylococci in 505 samples and S. aureus in 76 samples, of which 51 were oxacillin sensitive and 25 were oxacillin resistant. Sensitivity and specificity of the BinaxNOW® Test were 92% and 99%, respectively, compared to the phenotypic method. The Xpert MRSA/SA BC Assay showed complete concordance with phenotypic identification and antimicrobial susceptibility results. The combined rapid assays produced results within 2 hours and reduced the cost by 75% compared with the Xpert MRSA/SA BC Assay if used alone on all blood bottles.